Audit Quality Effects of an Individual Audit Engagement Partner Signature Mandate. (4th May 2014) - Blay, Allen D.; Notbohm, Matthew; Schelleman, Caren; Valencia, Adrian
<x xml:space="preserve">Abstract</x> The European Union recently mandated that audit engagement partners sign their name to the audit opinion. However, there is little evidence demonstrating whether such a mandate had any influence on audit quality. We examine the audit quality effects of a partner signature mandate by comparing multiple measures of audit quality in years after adoption of an audit partner signature mandate in the Netherlands, a country with no tradition of partner signatures, to the audit quality in years prior to adoption, as well as to the United Kingdom, a country with a similar legal and accounting environment, but which did not adopt partner‐level signatures at the same time. We detect no substantial change in audit quality using multiple measures and sample selection criteria. Although a null result cannot demonstrate that no effect exists, power tests suggest the lack of an economically significant effect. Our results support the arguments of practitioners who believe that mandatory partner signatures will not influence audit quality.